2014
DOI: 10.3109/21681805.2014.892150
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide, population-based study of prostate cancer stage migration between and within clinical risk categories

Abstract: Low-risk cases today have substantially lower tumor volume and PSA levels than low-risk cases diagnosed in 1998, indicating that outcomes in studies that recruited cases in previous decades represent worst case scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…First, we found that patients with high-risk disease treated with radical prostatectomy had a lower PSA level at diagnosis, as well as a lower rate of locally advanced disease and a higher rate of high grade prostate cancer over time. Changes in PSA level and clinical stage at diagnosis were to be expected after the introduction of PSA screening programmes; similar results were shown in a recent population-based study [19]. Moreover, such results confirmed previous studies that showed a stage migration towards more aggressive prostate cancer for patients treated with radical prostatectomy [11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…First, we found that patients with high-risk disease treated with radical prostatectomy had a lower PSA level at diagnosis, as well as a lower rate of locally advanced disease and a higher rate of high grade prostate cancer over time. Changes in PSA level and clinical stage at diagnosis were to be expected after the introduction of PSA screening programmes; similar results were shown in a recent population-based study [19]. Moreover, such results confirmed previous studies that showed a stage migration towards more aggressive prostate cancer for patients treated with radical prostatectomy [11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…In Denmark, PSA‐based early detection programs have never been recommended; however, laboratory data and trends in the incidence of PCa suggest that the use of PSA testing increased in the early 2000s . Although the effect of PSA‐based early detection on PCa‐specific mortality is still under debate, early detection has significantly increased the number of men diagnosed with localized and locally advanced disease . Randomized clinical trials (RCTs) investigating PSA‐screening have demonstrated a reduction in the incidence of de novo metastatic PCa, but this has not been investigated in large, population‐based studies …”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of PSA testing in Sweden also likely explain differences in clinical presentation and survival between the two otherwise similar Nordic countries with free public healthcare systems [11,12]. Almost 30% of men diagnosed with PCa in Sweden in 2011 were classified as low-risk while 11% had metastases at diagnosis [13] corresponding percentages in the current Danish cohort was 18% and 17%. In accordance with observations from Sweden and also USA, we found that treatment with curative intent was primarily used in men with clinically localized PCa, whereas men with higher risk disease were managed without curative intent [11,14].…”
Section: Discussionmentioning
confidence: 99%